EFEKTIVITAS PELAKSANAAN PERATURAN OMBUDSMAN RI NOMOR 58 TAHUN 2023 TENTANG CARA PEMERIKSAAN DAN PENYELESAIAN LAPORAN PADA OMBUDSMAN KALIMANTAN BARAT - Nessa Putri Andayu; S.Y Pudjianto; Jumadi Jumadi (The Indonesian Journal of Public Administration (IJPA), 2025)
In 2023, the processing of public reports at the West Kalimantan Ombudsman was not yet at the level of quality standards in terms of the time it takes to resolve reports. The purpose of the study is to explain how well the West Kalimantan Ombudsman is meeting the 2023 standard quality benchmarks of report resolution time and what factors influence it. The study is qualitative in nature and employs a descriptive methodology.. The methods of data collection were interviews and documentation studies, and the research subjects were Ombudsman representatives and the population. The findings reveal that the achievement of the standard quality benchmarks of report resolution time was not yet effective, as the productivity criterion revealed that 67 out of 136 reports were delayed; the adaptation to assistant shortages was not yet optimal, as the process of achieving time benchmarks did not involve PVL (Public Complaints Handling) and Prevention assistants; the job satisfaction of assistants was quite good but did not ensure the effectiveness of work because of the absence of regular training and capacity building by the institution. The inadequate number of assistants to satisfy the organizational demands, the slow coordination with the related agencies, particularly, at the clarification stage, the variety of working peculiarities of assistants that demand flexible managerial approaches, and the lack of particular report resolution time objectives in representative management are the factors that hinder effectiveness. The assistant job satisfaction was quite satisfactory, but the absence of regular training and capacity building also did not contribute to the best performance. It is recommended based on the findings that the West Kalimantan Ombudsman should enhance its working network by signing Memorandums of Understanding with regional heads in West Kalimantan and government agencies to speed up the resolution of reports.Keywords: Effectiveness; Ombudsman; Public Reports; Time Quality Benchmark